Ethnobiology of wonosobo batik: Biology education reference book based on local wisdom - Susi Setianingsih; Ericka Darmawan; Setiyo Prajoko (Biosfer: Jurnal Pendidikan Biologi, 2026)
Wonosobo batik motif interprets the rich nature, the geographical conditions, and the existing culture through distinctive motifs and utilizes several plant parts as its natural dyes. Utilizing the potential of flora and fauna in batik is not yet widely known by the public due to limited information. This study aims to determine the ethnobiological profile of Wonosobo Batik and to determine the feasibility of a reference book entitled "Ethnobiology of Wonosobo Batik" from a material and media perspective. The research methods use a qualitative approach(field study) followed by research and development (R&D) using the 4-D model developed by Thiagarajan, which was later limited to 3-D (Define, Design, Develop). Based on exploration result, 22 species of flora and fauna were identified as being used in Wonosobo Batik. These flora and fauna are classified in 16 order groups for flora and 3 orders for fauna. The order groups in flora are Brassicales, Apiales, Agaricales, Arecales, Solanales, Fabales, Myrtales, Sapindales, Poales, Malpighiales, Gentiales, Ericales, and the order groups in fauna are Psittaformes, Anseriformes, and Galliformes. Each ordo group has its own philosophical significance and benefits. The developed Reference Book was categorized as excellent, with a score 85.4% for material validity and 95% for media validity.